Exposure problem in multi-unit auctions - Hikmet Gunay; Xin Meng (Osaka University, Institute of Social and Economic Research (ISER), 2012)
We characterize the optimal bidding strategies of local and global bidders for two heterogenous licenses in a multi-unit simultaneous ascending auction. The global bidder wants to win both licenses to enjoy synergies; therefore, she bids more than her stand-alone valuation of a license. This exposes her to the risk of losing money even when she wins all licenses. We determine the optimal bidding strategies in the presence of an exposure problem. By using simulation methods, firstt, we show the frequency of inefficient allocation in the simultaneous ascending auction. Then, we show that the Vickrey-Clarke-Groves (VCG) mechanism may generate more revenue than the simultaneous ascending auction.
Keywords: D44; D82; 330; Multi-Unit Auctions; Vickrey Clarke Groves (VCG) mechanism; Exposure Problem; Synergies; Complementarity; Asymmetrische Information; Auktionstheorie; Theorie